DNIPRO UKRAINE REGIONAL SCIENTIFIC AND EDUCATIONAL CENTRES IN THE EUROPEAN INTERCULTURAL DIALOGUE (peer-review of the monograph: Ivanenko, O. A. Integration of the Dnipro Ukraine Regional Scientific and Educational Centres into the European Intellectual Space (Second Half of the 19th – Early 20th Centuries). Kyiv: Institute of History of Ukraine of the National Academy of Sciences of Ukraine, 2024. 555 p.) - HORBACHYK , Oksana; DUBYTSKA, Oksana (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
Peer-review of the monograph: Ivanenko, O. A. Integration of the Dnipro Ukraine Regional Scientific and Educational Centres into the European Intellectual Space (Second Half of the 19th – Early 20th Centuries). Kyiv: Institute of History of Ukraine of the National Academy of Sciences of Ukraine, 2024. 555 p.